Strengthening Students’ Islamic Character Through The Anak Beriman And Kepribadian Program At Sdn 2 Pangenrejo - Nasril Ahmad Fatah; Prawidya Lestari (Yayasan Azhar Amanaa Yogyakarta, 2026)
Strengthening Islamic character at the elementary school level is an essential effort in developing students who not only possess academic competence but also demonstrate religious attitudes, noble morals, discipline, and social responsibility. The ongoing phenomenon of a gap between students’ understanding of religious values and the implementation of Islamic behaviors in daily life encourages schools to develop religious habituation programs. This study aims to describe the implementation of the Program Anak Beriman (Faithful Children Program), analyze strategies for strengthening Islamic character in learning activities, and examine the impact of the program on the development of students’ religious character at SDN 2 Pangenrejo. This study employed a qualitative approach using a case study method. The research was conducted at SDN 2 Pangenrejo, with data sources consisting of the principal, teachers, representatives of students from grades 1–6, and parents. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles, Huberman, and Saldaña data analysis model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the (1).Program Anak Beriman was implemented through various religious habituation activities, including collective prayers, recitation of Asmaul Husna, Qur’an reading, memorization of daily prayers and short Qur’anic chapters, prayer practices, and religious social activities. (2).The strategies for strengthening Islamic character were carried out through habituation, teacher role modeling, student guidance, the use of learning media, and collaboration with parents. (3).The program has contributed positively to the development of students’ religious character, as reflected in their worship habits, discipline, politeness, responsibility, and concern for the surrounding environment. This study contributes by providing an overview of the implementation of Islamic character strengthening based on school culture, which can serve as a reference for elementary education institutions in developing sustainable character-building programs.